Knowledge, attitude and practice regarding rabies and the association of sociodemographic factors among school students in Northern Sri Lanka - Srinekethan, L.; Arulnesan, A. A.; Coonghe, P. A. D.; Murugananthan, K. (University of Jaffna, 2024)
Rabies is a 100% vaccine-preventable zoonotic disease. Despite vaccination efforts, insufficient awareness about seeking prompt medical care after an animal bite contributes to the continued prevalence of rabies in Sri Lanka. This study aimed to assess the Knowledge, Attitude, and Practice (KAP) regarding rabies and the association of sociocultural factors among school students in Northern Sri Lanka. A descriptive, school-based study was conducted among 715 advanced-level students from National schools in the Jaffna zone during September 2019. Proportionate stratified random sampling was used. A self-administered questionnaire, developed with expert input, assessed the Knowledge, Attitude, and Practice and the impact of sociocultural factors. Scores for each domain were categorized as poor, moderate, or good, based on predefined thresholds. The minimum and maximum possible scores ranged from 1 to 10 were given. Ethical clearance for this study was obtained from Ethical committee, Faculty of Medicine, University of Jaffna. Data were analyzed using SPSS 21 and the chi-squared test was used to assess the association between variables and, p-value less than 0.05 considered statistically significant. Among the participants, 58% were male, with a median age of 17 years (IQR: 16.5–19.5). Only 6% of students had “Good” knowledge, while 48.7% had a & “Moderate” understanding of rabies (mean score: 48.95±14.16). Attitudes were generally poor, with 32.2% displaying a good attitude (mean score: 53.59±25.20). Practices were notably lacking, with 73.1% showing poor practices (mean score: 31.72±20.23). Knowledge was associated significantly with the stream of study (p=0.027), attitudes (p=0.007) and practices (p=0.001). Practices were significantly associated with gender (p=0.001), study stream (p=0.009), and pet ownership (p=0.001). The study identified significant gaps in students’ knowledge, attitudes, and practices regarding rabies. Implementing rabies awareness programs for school students in Northern Sri Lanka is highly beneficial.
Keywords: Rabies; Knowledge; Attitude; Practice; Sociodemographic factors